Gendering the ’aqueous territory’: A study of free Afro-Caribbean women and spatial practices in Charlotte Amalie on St. Thomas in 1803 - Büron Frantzen, Anika (Culture and History: Student Research Papers, 2025)
This article examines how free Afro-Caribbean women shaped the transimperial space of Charlotte Amalie on St. Thomas in 1803. Using Ernesto Bassi’s concept of an aqueous territory, the study highlights women’s economic roles and mobility through an analysis of the 1803 Register of Free Afro-Caribbeans on St. Thomas. Focusing on migrants from Curaçao and Martinique, it shows how occupation, length of residence, and cultural competencies influenced integration. The article argues that free Afro-Caribbean women were not merely present in the free port but acted as spatial agents, actively contributing to the social and economic networks that defined the Caribbean’s interconnected colonial world.